2019
DOI: 10.3390/nano9030471
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Efficient Protocol for Preparing Residual-Free Single-Walled Carbon Nanotube Films for Stable Sensing Applications

Abstract: In this article, we report on an efficient post-treatment protocol for the manufacturing of pristine single-walled carbon nanotube (SWCNT) films. To produce an ink for the deposition, the SWCNTs are dispersed in an aqueous solution with the aid of a carboxymethyl cellulose (CMC) derivative as the dispersing agent. On the basis of this SWCNT-ink, ultra-thin and uniform films are then fabricated by spray-deposition using a commercial and fully automated robot. By means of X-ray photoelectron spectroscopy (XPS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 70 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…[ 19 ] C=O and C–O bonds are mainly present in oxidized CNTs. [ 20 ] These findings suggested that the SWCNTs possessed enough carboxyl groups to provide accessible conjugated sites for formation of composites. The typical XPS spectrum (Figure 1f) for Ag 3 d had two peaks centred at 373.7 and 367.7 eV, and associated with Ag 3 d 3/2 and Ag 3 d 5/2 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] C=O and C–O bonds are mainly present in oxidized CNTs. [ 20 ] These findings suggested that the SWCNTs possessed enough carboxyl groups to provide accessible conjugated sites for formation of composites. The typical XPS spectrum (Figure 1f) for Ag 3 d had two peaks centred at 373.7 and 367.7 eV, and associated with Ag 3 d 3/2 and Ag 3 d 5/2 .…”
Section: Resultsmentioning
confidence: 99%
“…The excitation voltage applied in all measurements was V DC = 0 and V AC = 500 mV in the frequency range from 100 Hz to 10 MHz. Calibration was done to compensate for the parasitic elements in agreement with previous work [36,37]. The sensor was placed in a climatic chamber VLC4006) from Vötsch Industrietechnik GmbH (Balingen, Baden-Wuerttemberg, Germany) with temperature and humidity control.…”
Section: Methodsmentioning
confidence: 99%
“…SWCNT suspensions were characterized by measuring the zeta potential as a function of pH using the microelectrophoresis technique assisted with laser Doppler velocimetry (Zetasizer NanoZS, Malvern, United Kingdom). The zeta potential of suspensions was determined at 25.0 ± 0.1°C, for pH values between 4 and 9, broader than the physiological pH range (6)(7)(8).…”
Section: Colloidal Characterization Of Swcnt Suspensionsmentioning
confidence: 99%
“…According to the number of graphene layers, CNTs are conventionally classified as Single-Walled-(SWCNT) or Multi-Walled-(MWCNTs) Carbon Nanotubes. Since their discovery, numerous studies have developed very creative CNTs applications, including multifaceted sensors, and those in nanotechnology, material science, electronics, optics, gas storage and biomedicine [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%